Failure to Thrive in a Middle-Aged Female: A Case of Congenital Incomplete Pancreas From a Rare Genetic Defect - Onyinye Ugonabo MD; Turki Mohamed MD; Murad Kheetan MD; Ahmed Sherif MD (SAGE Publishing, 2023)
Hepatocyte nuclear factor-1 beta (HNF1B) gene is predominantly expressed in the liver, kidney, lung, genitourinary tract, and pancreas. It is an important transcription factor that regulates pancreas development. Mutation or absence of this gene is rare and can cause incomplete pancreatic development known as the agenesis of the dorsal pancreas. This rare genetic abnormality is associated with other disorders like maturity-onset diabetes of the young, abnormal liver function tests, genitourinary tract malformation, pancreatitis, and renal cysts. Diagnosing this genetic abnormality is difficult, especially in patients presenting with symptoms specific to only one system. Management is based on disease manifestation and involves a multidisciplinary approach. Our case describes a 51-year-old female with poorly controlled diabetes mellitus and Mullerian duct anomalies who presented with abdominal pain, fatigue, dizziness, and electrolyte derangement. Contrast-enhanced computed tomography (CECT) of the abdomen showed a multicystic kidney and a pancreatic head with a missing body and tail. Further workup revealed an HNF1B mutation.